Umar Ibn al-khattab and Islamic Legal Innovation: a Study on Reality-Based Flexibility - Husnawadi (Mutawasith: Jurnal Hukum Islam, 2025)
The phenomenon of rigid and textual application of Islamic law in various contemporary judicial institutions highlights the need for a more adaptive and contextual legal approach. This study aims to describe the innovations and flexibility in the implementation of Islamic law during the caliphate of Umar ibn al-Khattab, a visionary leader known for his legal policies grounded in social realities. This research is crucial as a reference for actualizing Islamic law to remain relevant and responsive to the dynamics of modern society. This study employs a descriptive qualitative method, utilizing literature review techniques involving relevant sources such as classical and contemporary textbooks, encyclopedias, academic journals, and other secondary references. The collected data are critically analyzed and interpreted thematically. The findings reveal that Umar ibn al-Khattab innovatively interpreted and applied Islamic legal texts contextually, considering public welfare (maslahah), social conditions, and the nature of offenders. This indicates that Islamic law during Umar's era was characterized by its flexibility and responsiveness, serving as an ideal model for implementing Islamic legal principles in changing times.